Խորհրդային կայսրության կազմաքանդման հարցի շուրջ - Մարտիրոսյան, Շիրին (Զանգակ հրատ.)
Представленная статья показывает, что горбачевская перестройка была задумана как подготовка к сознательному разрушению СССР, втягиванию страны в мировую экономику и созданию «нового миропорядка ». Вместе с тем продемонстрировано, как тщательно утаивалась идея развала и какую роль сыграл внешний фактор в деле разрушения. The author of the article argues that the M. Gorbachev Reconstruction (Perestroyka) had deliberately been designed to cause the collapse of the Soviet Union, to drag the country in the world economy and lay a foundation to establish a “New World Order”. Meanwhile, the author demonstrates how the process of collapse was kept secretly, and the role of foreign factors contributed to that collapse.
Keywords: Գիտնականի մտորումներ; Պատմություն; Իրավաբանություն